(untitled) (Nóema, 2019)
The second half of the nineteenth century was a crucial moment for the institutionalization of psychology from European experimental studies that became increasingly popular in the United States. The relationship between pragmatist philosophy and biology is deeply linked to psychology, and in particular to the physiological and Darwinian psychology elaborated by William James. This article focuses on a portion of the much broader debate involving some of the leading American exponents of the new psychology with the intention of highlighting important methodological and theoretical issues that arose concerning the relationship between biology and philosophy within an evolutionary framework, issues in some ways still relevant today.